Microbiota-driven CXCL10-RHOA signalling in lactiplantibacillus plantarum lab12-induced neuroprotection against alzheimer’s disease / Lim Siong Meng ... [et al.] - Meng, Lim Siong; Ramasamy, Kalavathy; Abdul Majeed, Abu Bakar; Sabirin, Faezah (Faculty of Pharmacy, 2024)
Alzheimer’s disease (AD), which is the most prevalent cause of dementia in the world, is characterised by severe deficits in memory, cognition and motor functions. The burden of AD and other dementias accounts for an estimated 0.7% of the global population, translating to 51.6 million people worldwide [1]. In Malaysia, there are currently about 50,000 people living with AD. These are, however, underestimated figures as there are still many who remain undiagnosed, assuming that AD is a normal ageing process [2]. The causes of AD varied and not entirely understood [3].